G556 Elemental formula associated hypophosphataemic rickets. (May 2019) - Uday, S; Sakka, S; Davies, JH; Randell, T; Arya, V; Brain, C; Tighe, M; Allgrove, J; Arundel, P; Pryce, R; Högler, W; Shaw, NJ
Abstract : Objectives: Hypophosphataemic rickets (HR) is usually secondary to renal phosphate wasting but may occur secondary to reduced intake or absorption of phosphate. We describe a series of cases of HR associated with the use of Neocate®, an amino-acid based formula (AAF). Methods: A retrospective review of cases with HR associated with AAF use presenting to centres across the United Kingdom. Results: 10 cases were identified, over a 9 month period, all associated with Neocate ® use. The age at presentation was 5 months to 3 years. The majority (8/10) were born prematurely. Gastro oesophageal reflux disease (GORD) (6/10) was the most frequent indication for AAF use followed by cow's milk protein intolerance (CMPI) or allergy (CMPA). Radiologically apparent rickets was observed after a median of 8 months (range 3–15 months) of exclusive Neocate ® feed. The majority (7/10) were diagnosed on the basis of incidental findings on radiographs: rickets (6/10) or fracture with osteopenia (5/10). All patients had typical biochemical features of HR with low serum phosphate, high alkaline phosphatase, normal serum calcium and 25 hydroxyvitamin D. However, in all cases the tubular reabsorption of phosphate (TRP) was ≥96%. Phosphate supplementation resulted in normalisation of serum phosphate within 1 to 16 weeks, and levels remained normal only after Neocate ® cessation. In patients with sufficient follow up duration (4/10), normalisation of phosphate and radiological healing of rickets was noted after 6 months (range: 6–8 months) following discontinuation of Neocate ® . Conclusion: The presence of a normal TRP and resolution of hypophosphataemia and rickets following discontinuation of Neocate ® indicates this is a reversible cause likely mediated by poor phosphate absorption. Healthcare professionals diagnosing and managing GORD and CMPA/CMPI should be familiar with practice guidelines, the association of AAF Neocate ® with hypophosphataemia. Close biochemical surveillance is recommended for children on Neocate ®, especially in those with gastrointestinal co-morbidities, with consideration of a change in feed or phosphate supplementation in affected children.